Strategic Coordination Of Cultural Projects In Art Organizations: Modern Approaches To Sustainable Development (Wire Insights: Journal of Innovation Insights, 2026)
The article examines the transformation of logistics from an operational function into a strategic management instrument within contemporary art organizations. The study analyzes the role of logistics in coordinating cultural projects, managing information flows, integrating supply-chain processes, and supporting sustainable development in the creative economy. Particular attention is devoted to project logistics, information logistics, risk management, and the growing importance of logistics in museums, galleries, cultural centers, and exhibition institutions. The research applies systemic, analytical, and comparative approaches to evaluate the effectiveness of logistics mechanisms in cultural organizations. The findings demonstrate that modern logistics significantly improves project coordination, reduces organizational uncertainty, enhances communication efficiency, and strengthens the competitiveness of art institutions. The study concludes that logistics has become an essential component of strategic management in the cultural sector under conditions of globalization and digital transformation.